A General Pathway for the Synthesis of Gallastibenes containing Ga=Sb Double Bonds. Issue 36 (6th June 2018) - Krüger, Julia; Ganesamoorthy, Chelladurai; John, Lukas; Wölper, Christoph; Schulz, Stephan
Abstract: Reactions of three equivalents of LGa L=HC[C(Me)N(2, 6‐ i Pr2 C6 H3 )]2 with SbX3 (X=F, Cl, Br, I) proceed with insertion into the Sb−X bond, elimination of LGaX2, and formation of LGaSbGa(X)L (X=F1, Cl2, Br3, I4 ) containing a Ga=Sb double bond. In contrast, the 2:1 molar ratio reaction of LGa and SbCl3 initially gives the twofold insertion product [L(Cl)Ga]2 SbCl7, which could not be isolated due to its strong tendency toward elimination of LGaCl2 and formation of distibene [L(Cl)GaSb]2 5 at 25 °C or cyclotristibine [L(Cl)GaSb]3 6 at 8 °C. The formation of1 –6 can be rationalized by formation of the Ga‐substituted stibinidene L(X)GaSb as reaction intermediate. Abstract : A general pathway is presented for the synthesis of gallastibenes LGaSbGa(X)L (X=F1, Cl2, Br3, I4 ) containing Ga=Sb double bonds by reactions of three equivalents of LGa L=HC[C(Me)N(2, 6‐ i Pr2 C6 H3 )]2 with SbX3 . In contrast, the reaction of two equivalents of LGa with SbCl3 at 25 °C yields distibene [L(X)GaSb]2 5, whereas cyclotristibine [L(X)GaSb]3 6 is formed at 8 °C.